Proses Dokumentasi Keperawatan: Gangguan Persepsi Sensori Halusinasi Pendengaran pada Skizofrenia - Elina Aris Tiyani; Dian Prastiwi; Angga Sugiarto (Poltekkes Kemenkes Semarang, 2021)
Background: Schizophrenia is a psychosis, a type of mental illness characterized by distortions in thinking, perception, emotion, language, sense of self and behavior. One of the symptoms is hallucinations, hallucinations: hearing, seeing or feeling things in the absence of external stimuli. This sensory perception disorder includes all five senses. One of them is auditory hallucinations.Objective: to describe the implementation of the nursing process for mental health with impaired sensory perception, auditory hallucinations, Mrs. F at Prof.Dr. Soerojo Magelang.Methods: this research was conducted using a descriptive method. Collecting data by interview and observation on the nursing process in patients with auditory hallucinations.Results: there was an increase in knowledge and ability to control hallucinations,Conclusion: Nursing care for schizophrenic patients with hallucinations can increase knowledge and ability to control hallucination.